2012
DOI: 10.1371/journal.pone.0036288
|View full text |Cite
|
Sign up to set email alerts
|

The Contrasting Effect of Macromolecular Crowding on Amyloid Fibril Formation

Abstract: BackgroundAmyloid fibrils associated with neurodegenerative diseases can be considered biologically relevant failures of cellular quality control mechanisms. It is known that in vivo human Tau protein, human prion protein, and human copper, zinc superoxide dismutase (SOD1) have the tendency to form fibril deposits in a variety of tissues and they are associated with different neurodegenerative diseases, while rabbit prion protein and hen egg white lysozyme do not readily form fibrils and are unlikely to cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 48 publications
7
92
0
Order By: Relevance
“…conditions, PEGs can facilitate or inhibit protein aggregation [21,22]. PEG treatment after traumatic brain injury reduces the accumulation of -amyloid precursor protein in degenerating axons [23].…”
Section: Marta Kotormanamentioning
confidence: 99%
“…conditions, PEGs can facilitate or inhibit protein aggregation [21,22]. PEG treatment after traumatic brain injury reduces the accumulation of -amyloid precursor protein in degenerating axons [23].…”
Section: Marta Kotormanamentioning
confidence: 99%
“…3, prion protein is a GPI-anchored cell surface protein and the conversion of PrP from a normal soluble conformation PrP C to its pathogenic conformation PrP Sc is dramatically accelerated by crowded physiological environment containing high concentrations of polysaccharides and collagen. Our data suggested that prion-like proteins associated with neurodegenerative diseases are more inclined to form amyloid fibrils in crowded physiological environments than in dilute solutions [64,66,67]. The 'driving power' for fibrillization of prion-like proteins involves both the formation of an intermolecular or intramolecular disulfide bond and non-covalent interactions such as electrostatic interactions, hydrogen bonds, and hydrophobic interactions, which could be enhanced by crowded physiological environments [66].…”
Section: Prion-like Protein Aggregation In Crowded Physiological Envimentioning
confidence: 81%
“…It is known that in vivo human prion protein and its pathogenic mutants, human Tau protein and its pathogenic mutants, and human SOD1 pathogenic mutants have the tendency to form amyloid deposits in many different kinds of tissue and they are associated with different kinds of neurodegenerative diseases [64]. However, it is hard to distinguish the factors that affect prion-like protein aggregation in vivo because of the interaction network between proteins and proteins, proteins and nucleic acids, and so on.…”
Section: Prion-like Protein Aggregation In Crowded Physiological Envimentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies showed that a few animals such as rabbits exhibit low susceptibility to be infected by the PrP Sc (Vorberg et al, 2003;Khan et al, 2010;Barlow & Rennie, 1976;Fernandez-Funez et al, 2009;Korth et al, 1997;Courageot et al, 2008;Vilette et al, 2001;Nisbet et al, 2010;Wen et al, 2010aWen et al, & 2010bZhou et al, 2011;Ma et al, 2012). Now experimental structural data for rabbit PrP C (RaPrP C ) is available from the Protein Data Bank (PDB bank: http://www.rcsb.org/).…”
Section: The Role Of Prpmentioning
confidence: 99%